HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG CUCI TANGAN YANG BENAR DENGAN KEJADIAN DIARE PADA BALITA - Ridwan, Ahmad; Ardiansyah, Rico (Jurnal AKP, 2012)
Diarrhea is the state of the frequency of bowel movements more than four times in infants and more than three times in children with the consistency of watery feces, the factors are the environmental causes of diarrhea, how to wean poor, and individuals. Washing hands with soap is one of the actions of sanitation by cleaning hands and fingers with water and soap to be clean and germ decided chain. The purpose of this study is to determine the relationship of mother knowledge about proper handwashing on diarrhea in infants posyandu Kandangan.Design in this study is correlational research that examine the relationship between variables, research can be done by finding, describing a relationship, estimating, testing based on existing theory. The population is all children in the neighborhood health center Kandangan, research sample was all children in attendance at the neighborhood health center on 22 March 2010 or during the conduct of research. In this study using cross sectional analytic study of this kind of research that emphasizes the time of measurement / observation of the independent and dependent variable data only once, at one time. But not all research subjects should be observed on the same day or time, and to know the relationship between correlations using Spearman correlation.The results showed that Spearman correlation (Ï) = 0.030. This indicates a positive number, which means there is a relationship between maternal knowledge about proper hand washing with diarrhea in infants with sigfinikan test (sig. Î¡ = 0.030 <Î± = 0.05) with 5% error level (Î± = 0.05)From the research it is suggested to prevent occurrence of diarrhea in infants not only with proper hand washing but also by keeping the environment clean, correct way of weaning, and the pattern of a clean and healthy living. Keywords: knowledge, maternal hand-washing, the incidence of diarrhea, infant